(6y-5x)(3y-7x+4)=

Simple and best practice solution for (6y-5x)(3y-7x+4)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (6y-5x)(3y-7x+4)= equation:


Simplifying
(6y + -5x)(3y + -7x + 4) = 0

Reorder the terms:
(-5x + 6y)(3y + -7x + 4) = 0

Reorder the terms:
(-5x + 6y)(4 + -7x + 3y) = 0

Multiply (-5x + 6y) * (4 + -7x + 3y)
(-5x * (4 + -7x + 3y) + 6y * (4 + -7x + 3y)) = 0
((4 * -5x + -7x * -5x + 3y * -5x) + 6y * (4 + -7x + 3y)) = 0

Reorder the terms:
((-20x + -15xy + 35x2) + 6y * (4 + -7x + 3y)) = 0
((-20x + -15xy + 35x2) + 6y * (4 + -7x + 3y)) = 0
(-20x + -15xy + 35x2 + (4 * 6y + -7x * 6y + 3y * 6y)) = 0

Reorder the terms:
(-20x + -15xy + 35x2 + (-42xy + 24y + 18y2)) = 0
(-20x + -15xy + 35x2 + (-42xy + 24y + 18y2)) = 0

Reorder the terms:
(-20x + -15xy + -42xy + 35x2 + 24y + 18y2) = 0

Combine like terms: -15xy + -42xy = -57xy
(-20x + -57xy + 35x2 + 24y + 18y2) = 0

Solving
-20x + -57xy + 35x2 + 24y + 18y2 = 0

Solving for variable 'x'.

The solution to this equation could not be determined.

See similar equations:

| 3/4g=28 | | 6x+16=3x+17 | | 3h-6+2h=-2+h | | X^2-2ax-1=0 | | 5(2-x)-3(4-2r)=20 | | 2b+3=b+19 | | 15x^3+3x= | | 3l-6+2l=-2+l | | 6i/5+3i= | | [2x-2]=6 | | 5y=7x+2 | | 189=9-9x | | -(0.79k+0.227)=-(2.09k+0.838) | | 6/4+6i= | | p^3(e^5p-7)-(6p/2_p^2) | | lnx+2=7+lnx-1 | | lnx^3=7lnx | | 5/7×3/4=? | | 4i/8+2i= | | -2x+2=5y | | (2x-1/3)^2 | | 1/3(9h*h-6h) | | 9x/2-10x=7 | | 3(2x+1)+4=24 | | 7x^2-48x+7=0 | | 1/2-1/8=? | | 17-p=7p-13 | | 2x^5-18x^3-2x^2+18=0 | | ln(x+2)=7+ln(x-1) | | 5/12=K-1/3 | | 3n-8(8-8n)=338 | | 3p=-2/3 |

Equations solver categories